ответ: x ₁,₂ = [- 5 ± √( 4√26 - 11 ) ]/2 .
Пошаговое объяснение:
( x² + 3x + 6 )( x² + 7x + 16 ) = 41 ; перетворюємо множники :
[ x² + 5x + 11 - ( 2x + 5 )] * [ x² + 5x + 11 + ( 2x + 5 )] = 41 ; це різниця квадратів :
( x² + 5x + 11 )²- ( 2x + 5 )² = 41 ;
( x² + 5x + 11 )² - 4х² - 20x - 25 - 41 = 0 ;
( x² + 5x + 11 )² - 4 ( x² + 5x + 11 ) - 22 = 0 ;
Вводимо нову змінну : z = x² + 5x + 11 , ( z > 0 , бо D < 0 ) .
z² - 4z - 22 = 0 ;
D = 16 + 88 = 104 = 4 * 26 > 0 ; z₁ = 2 - √26 < 0 ( не підходить ); z₂ = 2 + √26 ;
Повертаємось до змінної х :
x² + 5x + 11 = 2 + √26 ;
x² + 5x + 9 - √26 = 0 ; рішаємо це квадр. рівняння і одержимо :
x ₁,₂ = [- 5 ± √( 4√26 - 11 ) ]/2 .